The Goodbye Quilt - Wiggs, Susan (Thorndike, Me. : Center Point Pub., 2011)
Linda Davis, the owner of a shop where women gather with their quilts commemorating important events of their lives, and her daughter Molly share one last adventure together as Molly goes off to college, making special memories along the way.
Keywords: Quilting -- Fiction; Mother-daughter relationship -- Fiction; Travel -- Fiction; Large print books